Drought resistance enhanced by tree species diversity in global forests - Liu, Dan; Wang, Tao; Peñuelas, Josep; Piao, Shilong (Nature geoscience, 2022)
Restoring species diversity is proposed as a strategy to improve ecosystem resistance to extreme droughts, but the impact of species diversity on resistance has not been evaluated across global forests. Here we compile a database that contains tree species richness from more than 0.7 million forest plots and satellite-based estimation of drought resistance. Using this database, we provide a spatially explicit map of species diversity effect on drought resistance. We found that higher species diversity could notably enhance drought resistance in about half of global forests but was spatially highly variable. Drought regimes (frequency and intensity) and climatic water deficit were important determinants of differences in the extent that species diversity could enhance forest drought resistance among regions, with such benefits being larger in dry and drought-prone forests. According to a predictive model of species diversity effect, the conversion of current monoculture to mixed-species tree plantations could improve drought resistance, with the large increase in dry forests. Our findings provide evidence that species diversity could buffer global forests against droughts. Restoration of species diversity could then be an effective way to mitigate the impact of extreme droughts on large scales, especially in dry and drought-prone regions. Tree species diversity promotes drought resistance in nearly half of global forests, according to a global analysis of the relationship between species richness and drought-induced changes in forest productivity.